Functional Constipation and the Gut Microbiome in Children: Preclinical and Clinical Evidence - Avelar Rodriguez, David; Popov, Jelena; Ratcliffe, Elyanne M.; Toro Monjaraz, Erick Manuel (Frontiers in Pediatrics, 2021)
Functional constipation is a common condition in childhood with significant impacts on quality of life and on utilization of health care resources. Functional constipation is characterized by decreased bowel movements and/or hard stools, which cause significant distress for children and their caregivers. While the term “functional” may imply the absence of organic causes with a focus on behavioral aspects, 40% of children continue to have symptoms beyond conventional management with 1 in four children continuing to experience constipation into adulthood. The refractory and chronic nature of constipation highlight the importance of considering a range of pathophysiological mechanisms, including the potential role of the gut microbiome. In this review, we provide an overview of preclinical and clinicals studies which focus on the potential mechanisms through which the gut microbiome might contribute to the clinical presentation of functional constipation in pediatrics.